Association between clinical parameters and risk of sepsis - Jongprasitkul, Nahatai; Petchratchatanon, Watchara; Charanyananda, Chatchasa (Chulalongkorn Medical Journal, 2023)
Background : Sepsis is a severe life-threatening condition and has a great diversity in symptoms that causes a rapid response of inflammation; as a result, it might damage the internal organs throughout the body. Nowadays, there is insufficient medical instrument and reliable treatment strategies that provide a promising diagnosis which can indicate the right sepsis condition. The aim of this research is to improve the clinical judgment, which might lead to earlier aggressive therapeutic interventions. Objectives : To study the association and risk factors between emergency department patients with sepsis. Methods : In all, 400 retrospective medical data records among emergency department patients were retrieved from a variety of sources (retrospective chart reviews). The samples were divided into culture positive and culture negative results of sepsis. After that the data were analyzed statistically to determine the relationship and risk factors in sepsis patients. Results : This study showed that sepsis was associated with male gender, diabetes mellitus, chronic kidney diseases, alcohol dependence, low hemoglobin level (less than 10 g/dL), albumin (less than 3.5 g/dL), lactate (more than 2.1 mmol/L), systolic blood pressure (less than 90 mmHg), respectively. It was also found that the risk factors were corresponding to diabetes mellitus (P = 0.033), chronic kidney disease (P = 0.008), low hemoglobin level (less than 10 g/dL) (P = 0.001), albumin (less than 3.5 g/dL) (P = 0.043), systolic blood pressure (less than 90 mmHg) (P = 0.001). Conclusions : Sepsis is a common condition which is often seen in emergency department. It is severely harmful and needs to be treated urgently. We found that the systolic blood pressure less than 90 mmHg was associated with the highest risk. Hopefully, this research could be an alternative to supplement the diagnosis and treatment of patients with sepsis in the future.